MOTHER TONGUE MEDIUM OF INSTRUCTION AS CORRELATE OF PUPILS ACADEMIC ACHIEVEMENT IN BASIC SCIENCE IN AWKA SOUTH LOCAL GOVERNMENT EDUCATION AUTHORITY - Bosah, Ifeoma Patience; Okika, Chinyere Love; Anozie, Abigail Cherechi (Journal of Early Childhood and Primary Education, 2025)
This study explored mother tongue medium of instruction as correlate of pupil’s academic achievement in basic science in Awka South Local Government Education Authority of Anambra State. Two purpose of the study, two research questions and two null hypotheses tested at 0.05 level of significance guided the study. Correlational research design was adopted for the study. The population consisted of 665 public primary school teachers in the 45 public primary schools in the area. Using simple random sampling technique of balloting without replacement, 200 teachers were selected as the sample for the study. Mother Tongue Medium of Instruction as a Correlate of Pupils Academic Achievement in Basic Science in Primary Schools (MTMICPAABSPS) Questionnaire was used to collect data on pupils’ use of  mother tongue in basic science, while data for academic achievement was collected from the annual result record sheets (pupils’ annual cumulative result of 2022/2023 academic session) in each of the sampled schools. Face and content validity of the instrument was determined by three experts; one in the Department of Early Childhood and Primary Education and one in Measurement and Evaluation in the Department of Educational Foundations both from the Faculty of Education, Nnamdi Azikiwe University, Awka and a Basic Science classroom teacher in Awka South. Cronbach Alpha was employed for the reliability of the instrument and reliability coefficient of 0.81 was obtained. Data collected with the aid of three research assistants who were basic science classroom teachers were analysed using Pearson Product Moment Correlation Coefficient for the research questions while the hypotheses were tested also using significance of the correlation at 0.05 alpha level. Findings of the study revealed among others that there is a high positive relationship between mother tongue and pupils’ academic achievement in basic science in primary schools. there is no significant relationship between male and female pupils’ use of mother tongue and their academic achievement in basic science in primary schools in Awka South Local Government Education Authority. It was concluded that the use of mother tongue as a medium of instruction has the potential to improve understanding and knowledge impartation in the classroom, and, by extension, improve academic achievement since mother tongue is the language with which the pupils use to create their own knowledge. The study recommended that Federal government should further re-enforce the use of mother tongue as recommended in National policy of Education as a medium of instruction at the lower level of basic education for effective and efficient teaching and learning to take place among others.
Keywords: Language; Mother Tongue; Basic Science; Academic Achievement